E-Commerce Pada Pasar Kerajinan Seni UMKM Batung Taba, Padang Sumatera Barat - Saputra, Heru; Trianda, Mulia; Elizamiharti, Elizamiharti; Stephane, Ilfa; Meta, Monanda Rio; Rajab, Rajab (SMART : Jurnal Teknologi Informasi dan Komputer, 2023)
This study aims to design an online-based art market information system for Batung Taba SMEs to help business actors to market their products digitally and reach a wider market share, especially in the field of arts crafts. Based on the results of observations made that Batung Taba SMES business actors do not yet have an information system which results in the sale of art products not being so widespread. This also makes it difficult for consumers to find information and the availability of goods. The research method uses the waterfall model with UML design tools. The result of this research is that the system built is expected to be able to increase the marketing of art products for the Batung Taba SMES business actors